A comprehensive review on power flow controller devices in transmission line - Saifuddin A.S.; Kamil K.; Hashim H. (Universiti Teknikal Malaysia Melaka, 2023)
This paper will review about power flow controller which is one of the Flexible AC Transmission System (FACTS) devices. FACTS devices is being used to increase the power transfer capability of transmission system and to regulate power flow over transmission line. Besides that, FACTS devices also being used in minimizing power losses in transmission system. The power flow controller devices being used in controlling power flow in a transmission system, to increase the transmission capacity, regulating the voltage and optimizing the stability of the transmission system. By using the power flow controller devices, it will prevent from a transmission line to be overloaded. There are a few types of power flow controllers being used nowadays such as Unified Power Flow Controller, Interline Power Flow Controller, SMART Power Flow Controller, Dynamic Unified Power Flow Controller, and last but not least which is a hybrid type of power flow controller is Interline Unified Power Flow Controller which is a combination of unified and interline design of power flow controller. For this paper, the content will focus on two types of power flow controller which are Unified Power Flow Controller (UPFC) and Interline Power Flow Controller (IPFC) because these two controllers are being widely used in the transmission system. The reasons of choosing UPFC and IPFC are because of the simplest connection yet most efficient devices to use among FACTS devices to improve the power system stability in the transmission system. As transmission system has a single line or multi-line system, these both controllers will play their role in controlling each system. For UPFC, it will control the single line system. If there is a multi-line system, it is inefficient to use UPFC as the devices need to be placed on each line and it will increase the costing. Therefore, IPFC can be used as the function is to control multi-line transmission system. This paper will review these two controllers in terms of their functions, operations and advantages for using the controllers in transmission system. 2016, Universiti Teknikal Malaysia Melaka. All rights reserved.